Erratum: Analysis of MSMEs' Cassava Production Efficiency Using a Comparison of Machine Learning Models in Jember Regency - Danang Kumara Hadi; Yuta Sato (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2026)
This Erratum relates to the following article:Hadi, D.K., Sato, Y., 2025. Analysis of MSMEs' Cassava Production Efficiency Using a Comparison of Machine Learning Models in Jember Regency. Agroindustrial Journal 12(1), 16–26. https://doi.org/10.22146/aij.v12i1.106018The publisher regrets that, due to a production error, the publication metadata on page 1 of the published PDF version of the article (DOI: 10.22146/aij.v12i1.106018) contained incorrect dates. The incorrect information appeared as: “Received: May-23-2025; Accepted: June-25-2025; Published: June-30-2025”. The correct dates are: “Received: April 15, 2025; Accepted: June 25, 2025; Published: June 30, 2025”.The editorial office regrets the error.